Karakter Tokoh dalam Novel "Dalam Pelukan Rahim Tanah" Karya Jemmy Piran (Pendekatan Psikoanalisa Sigmund Freud) - Eyen, Verena; Nai, Firmina Angela; Djokaho, Margareta P. E (Jurnal Lazuardi, 2025)
This research is entitled “Dalam Pelukan Rahim Tanah by Jemmy Piran”. The purpose of this study is to describe the character of the main character Bango in the novel in the Dalam Pelukan Rahim Tanah By Jemmy Piran. This research was conducted using the psychoanalysis Theory of Sigmund Freud. The theory of Sigmund Freud maps human mental as a personality sistem that is divided inti Id, Ego and Superego. the data in this research are collect ed from the novel Dalam Pelukan Rshim Tanah by Jemmy Piran, in the form of word, phrases, sentences and paragraphs. The method used in this research is Descriptive Qualitativ. The results of data analysis in this study with the collaboration between three personalyti Id, Ego and Superego, that Bango Figures have seven character include, compassionate, kind, patien, angry, rude, vested and anxious. Therefore, it can be concluded that the character of the main character Bango is classified into two basic characters, namely good and bad characters, which are a collaboration between the three personality systems of id, ego, and superego. The good character includes: loving, good, and patient. Meanwhile, the bad character includes: angry, harsh, vengeful, and anxious. Thus, in human personality, there are various characters that make a person's personality different from others. Keywords: Character, Main Character, Novel, Psychoanalysis